Simulation of lightning surges on tower transmission using PSCAD/EMTDC: a comparative study - Zakaria, Z.; Bashi, Senan M.; Mailah, Nashiren Farzilah; Othman, M. R.; Osman, H. (IEEE, 2002)
This paper describes the analytical and the experimental responses of the surges strike on the transmission line towers. A new method of calculating transmission tower surge response has been proposed. It has been found that the tower surge response calculated by the proposed method has a close agreement with the measured tower surge response obtained from scale model and field tests. Without the use of simulation program, this topic might be difficult to understand. PSCAD/EMTDC has been selected as the software used to generate the appropriate data needed to graphically demonstrate this phenomenon.